Protection of SBSN Debtors (Article 6 Of Law 19/2008 and Article 31 of Law 21/2011) - Widaningsih, W (Proceedings International Conference on Education Innovation and Social Science, 2022)
Legal protection is one element of improving aspects of law enforcement in a country. Legal protection is given by the state to its people in order to create stability, including in economic and legal terms. One of the financial instruments that can support APBN funds is the issuance of State Sukuk or better known as State Sharia Securities (SBSN). The purpose of this study is related to its compliance with sharia principles, its ability to provide legal protection for debtors as a form of legal certainty, which is transparent and accountable. Normative research is used in this study and uses a descriptive type of research. The results of the study show that the regulation on the legal protection of debtors in SBSN refers to Article 6 of Law No. 19 of 2008 concerning SBSN, as well as Article 31 of Law No. 21 of 2011 concerning the Financial Services Authority. SBSN in terms of issuance is carried out directly by the Government or through the SBSN Issuing Company, and the issuance company is determined by the minister. Article 31 states that further provisions regarding consumer and public protection are regulated by OJK regulation No. 1 /POJK.07/2013 concerning Consumer Protection in the Financial Services Sector which contains about increasing the trust of investors and consumers in every activity and business activity in the financial services sector, and providing opportunities and opportunities for development for Financial Services Businesses in a fair, efficient and transparent.+